PESANTREN SEBAGAI LEMBAGA DAKWAH PERUBAHAN SOSIAL BUDAYA - Akramun Nisa (Ash-Shahabah : Jurnal Pendidikan dan Studi Islam, 2021)
As educational and propaganda agencies, Islamic Boarding Schools have played an important social role, which acts as a social change and culture change. Islamic Boarding schools are institutions that can change the structures of ideas and thoughts in society and also change the various cultures that exist in the community. The main topic of this research is the existence of Islamic boarding school as propaganda agencies conduct socio-cultural changes in society. Descriptive approach is used to describe the characteristics of the boarding school, the purpose and function as institutions of education and propaganda to tafaqquh fi al-din through the study of classical science, kitab kuning. The findings of this study, that as agents of social and cultural change, schools play a role in three lines, namely: (1) tafaqquh fi al-din through educational institutions and propaganda; (2) Teaching Kitab Kuning through a dialogical approach, critical, 3) Investment of morals al-karimah in boarding schools and surrounding communities.